Investigation of the Presence of Heavy Metals in the Progression of Multiple Sclerosis - Yilmaz, Muhammed Zulfu; Gonen, Murat (Galenos Publ House, 2023)
Objective: Multiple sclerosis (MS) etiology studies show that the disease is multifactorial. While genetic features are more prominent at the beginning of the disease, the existence of environmental triggers that may cause the progression of the disease is still a subject of research. Materials and Methods: We evaluated 101 MS patients sharing the same geographical area. We performed heavy metal analysis in the blood and hair tissues of these patients. Of these patients, 67 were in the relapsing remitting MS (RRMS) group and 34 were in the progressive MS (PMS) group. Results: Samples were analyzed using the X Series 2 model (ICP MS) instrument. In hair samples, aluminum (Al) was found to be 8.98 mu g/g in the PMS group and 3.01 mu g/g in the RRMS group (P < 0.001). Unlike Al element, magnesium (Mg), calcium (Ca), cobalt (Co), zinc (Zn) and strontium (St) elements were observed to be higher in the RRMS group. RRMS for median Ca: 931 mu g/g, PMS: 400 mu g/g (P < 0.001); RRMS for Mg: 118 mu g/g, PMS: 50 mu g/g (P < 0.001); For Co RRMS: 0.0150 mu g/g, PMS: 0.0075 mu g/g (P = 0.008); RRMS for Zn: 138 mu g/g, PMS: 101 mu g/g (P = 0.008); For St RRMS: 4.76 mu g/g, PMS: 3.70 mu g/g (P = 0.008). With these results, we thought that Al excess or Mg, Ca, Co, and Zn deficiencies might be associated with MS progression. The mercury (Hg) blood level was slightly low in PMS. This finding was not correlated with hair samples (P = 0.047). The relationship between blood Hg level and RRMS should be evaluated separately. Conclusion: We could not find any study comparing PMS forms and RRMS subtypes in terms of heavy metals. In particular, it is necessary to focus on the Al element.
Multipl Skleroz Progresyonunda Ağır Metal Varlığının Araştırılması
Keywords: Multiple sclerosis; progression; heavy metals; aluminum